Gamma-Al2-xMxO3 +/- y (M = Ti4+ through Ga3+): potential pseudo-3D mesoporous materials with tunable acidity and electronic structure - Mathew, Thomas; Sivaranjani, Kumarsrinivasan; Gnanakumar, Edwin S.; Yamada, Yusuke; Kobayashi, Tetsuhiko; Gopinath, Chinnakonda S. (Journal of Materials Chemistry, 2012)
A simple and highly efficient surfactant-free sol-gel process has been developed to obtain nanocrystalline mesoporous gamma-Al2O3 and metal ion incorporated mesoporous gamma-Al2O3 with general formula gamma-Al2-xMxO3 +/- y (where M = Ti4+ through Ga3+). Any one of the first row transition metal (TM) ions along with Ga3+ could be introduced into the gamma-Al2O3 framework in a direct one-pot synthesis process. The generality of the present synthesis recipe for metal ion incorporation in gamma-Al2O3 was demonstrated by preparation of an Al-Ga-M ternary oxide system with the metal ion composition of general formula Al9GaTM (TM = Ti4+ to Zn2+) and their characterization through various physicochemical and spectroscopic techniques. The mesoporous gamma-Al2-xMxO3 +/- y materials showed a BET surface area in the range of 200-400 m(2) g(-1) with a narrow pore size distribution. Wormhole mesoporosity makes the material pseudo-3D (p3D) with a small pore depth of few nm (<10 nm). Metal ions in gamma-Al2O3 lead to changes in the acidity and electronic environment. XRD, TEM, and Al-27 MAS NMR studies demonstrate that the sol-gel process and the disordered mesoporous structure allow Ga and TM ions to be highly distributed and integrated in the gamma-Al2O3 framework. The efficacy of these materials in catalysis has been successfully evaluated for steam reforming of dimethylether: Ni, Cu and Zn containing Al9GaTM oxides showed high activity and stability. The smaller mesochannel depth (<10 nm) and pseudo-3D characteristics that arise due to the wormhole-type disordered mesoporous framework of these alumina materials facilitate mass transport through them without any leaching of metal ions out of the lattice and pore blocking during the reaction, which makes them attractive in catalysis. This preparation method is versatile enough to be used for a reproducible synthesis of metal ion incorporated mesoporous gamma-Al2O3 by varying the metal content and their combinations, and it is expected that many other metal ions could be introduced into the lattice framework for a variety of applications by tuning acidity and electronic structure.

Green chemistry approach to styrene from ethylbenzene and air on MnxTi1-xO2 catalyst - Negi, Sanjay Singh; Venugopalan, Aswathy Thareparambil; Raja, Thirumalaiswamy; Singh, Anand Pal; Gopinath, Chinnakonda S. (RSC Advances, 2014)
Styrene (ST) is an industrially important commodity chemical, and design of a suitable catalyst, which provides high ethyl benzene (EB) conversion and styrene selectivity at Lower temperature with sustainable activity, is one of the major challenges in the field of heterogeneous catalysis. Manganese incorporated in titania (MnxT1-xO2) anatase Lattice, prepared via the solution combustion method, was evaluated for oxidative dehydrogenation (ODH) of EB with O-2 or air. MnxTi1-xO2 catalysts were characterized by different physiochemical methods. Up to 15% Mn could be introduced into the TiO2 Lattice. TEM and XRD indicate disordered mesoporosity, further confirmed by adsorption isotherm analysis. MnxTi1-xO2 catalysts were evaluated for ST synthesis from EB using air or oxygen as oxidant between 440 and 570 degrees C. Reaction conditions have been varied systematically, such as catalyst composition, and EB/air/O-2 flow. MnxTi1-xO2 shows sustainable 55% styrene yield for 45 h without deactivation under optimum conditions. A thorough analysis of spent catalysts demonstrates the conversion of initial anatase phase MnxTi1-xO2 to Mn3O4 supported on the rutile (R) phase of TiO2. The above change occurs in the first few hours of reaction and the Mn3O4 on R-TiO2 phase is the active phase of the catalyst and responsible for sustainable activity for Longer duration.

Gas-solid interaction of H-2-Ce0.95Zr0.05O2: new insights into surface participation in heterogeneous catalysis - Jain, Ruchi; Dubey, Anjani; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S. (Catalysis Science & Technology, 2016)
A direct interaction between a reduction medium (H-2) and a Ce0.95Zr0.05O2 (CZ) solid surface was explored through ambient pressure photoelectron spectroscopy (APPES), with conventional X-ray and He-I photon sources, in H-2 atmosphere up to 0.1 mbar pressure and 773 K. A porous CZ thin film was prepared by a combination of sol-gel and spin-coating methods, and was employed to understand the redox nature of ceria under reduction conditions. The maximum of 45% Ce3+ along with the corresponding oxygen vacancy was observed due to reduction. An unprecedented decrease in the valence band (VB) energy up to 1.4 eV was observed on reduction along with a narrowing of VB. The highest occupied energy band derived from Ce 4f also shifts closer to E-F. H-2 molecular vibration observed in VB-APPES was employed as a probe to explore the surface potential changes along with the dynamic change in the nature of the surface under reduction conditions. The surface potential decreases by 0.27 eV up to 673 K, and then it reverts by 0.24 eV on further reduction at 773 K for different reasons. Further, an enhancement in the Ce 5d-O 2p interaction occurs at the expense of the Ce 4f-O 2p interaction under the above reduction conditions. Vacuum annealing and H-2 reduction after that show significantly more VB shift and enhanced reduction than H-2 reduction alone. Although Ce reduction occurs on high temperature vacuum annealing of CZ, a significantly lower amount of oxygen vacancies appears. This study shows the dynamic changes in the nature of the surface due to a gas (H-2)-solid (CZ) interaction and ensuing electronic structure changes that influence heterogeneous catalysis. It also underscores the necessity to study the catalytic materials under in situ conditions or closer to that.

Green leaf to inorganic leaf: a case study of ZnO - Sathu, Naveen K.; Devaraji, Perumal; Gopinath, Chinnakonda S. (Journal of Nanoscienceand Nanotechnology, 2016)
Can we use green leaves, available freely in our gardens, as a template for making inorganic leaf, while retaining the nanospace available within the leaf architecture. The answer is 'yes', and it is demonstrated with inorganic leaf made up of ZnO, by intercalating Zn2+ ions into the porous channels of the champa (Plumeria, Magnolia champaca) tree leaves. TEM studies reveal a variety of macro-micro-nanospace available in the inorganic leaf ZnO (IL-ZnO), and suggest the possibility of exploiting the same to produce natural nano-architecture for various applications. A speciality of the present work is the maximum suppression of defects in photoluminescence of IL-ZnO leaf, compared to the commercial ZnO, which is exploited for light harvesting through chemical conversion. Benzene to phenol conversion was studied in UV light and IL-ZnO show significant conversion and yield demonstrating C-H activation at ambient temperature.

Gas-solid interactions with reactive and inert gas molecules by NAPUPS: can work function be a better descriptor of chemical reactivity? - Ghosalya, Manoj Kumar; Reddy, Kasala Prabhakar; Mhamane, Nitin B.; Ranjan, Ravi; Gopinath, Chinnakonda S. (Physical Chemistry Chemical Physics, 2020)
The gas-phase vibrational spectra of reactive (H(2)and O-2) and inert gases (N(2)and Ar) have been studied by near-ambient pressure (NAP) ultraviolet photoelectron spectroscopy (NAPUPS) up to 0.3 mbar pressure. The results obtained are divided into two parts and discussed. In the first part, the photoelectron spectra of monoatomic Ar and some homonuclear diatomic molecules, such as H-2, O-2, and N-2, have been recorded by NAPUPS and the effect of pressure on their energy position has been studied. It has been demonstrated that NAPUPS could be an essential tool to determine the intermolecular or interatomic interactions. In the second part, we have evaluated the influence of different solid surfaces on the binding energy (BE) position, the pattern of the vibrational features of diatomic N(2)molecules, and the first atomic levels (3p(3/2)and 3p(1/2)) of monoatomic Ar. It has been observed that with a change in the (electronic/chemical) nature of the surface, the BE of the above features also changes and reflects the change in the work function (phi) of the material. It is to be noted that Ar is an inert/noble gas and N(2)is the most stable molecule, and the above changes observed underscore that they can be employed as probe atoms/molecules to explore even the minor changes that occur on a solid surface due to a variety of reasons. Further, if the solid surface undergoes any chemical/electronic changes due to gas-solid interaction, such as oxidation/reduction, the phi of the surface changes again; this highlights the precise identification of the changes that occur under the reaction/measurement conditions. Therefore, the change in the BE of the gas-phase features can be used to determine even the minor changes in the phi of solid surfaces during the reaction or due to the reaction. The present findings have implications in probing the surface changes that occur in any surface-dependent phenomena, such as heterogeneous catalysis, electrochemistry, and materials that are predominantly controlled by surface contribution, such as layered (2D) materials, nanomaterials.

Green route for carbonylation of amines by CO2 using Sn-Ni-O bifunctional catalyst and theoretical study for finding best suited active sites - Kulal, Nagendra; Vetrivel, Rajappan; Gopinath, Chinnakonda S.; Ravindran, Rahul K.; Rao, Vinod N.; Shetty, Manjunath; Shrikanth, R.; Rangappa, Dinesh; Shanbhag, Ganapati V. (Chemical Engineering Journal, 2021)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Reaction between n-alkylamine and CO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> has gained interest due to the demand for the dialkylurea for various applications. For the first time, the tool <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Mathematica<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> was used to analyze the experimental data with an idea to derive an equation which determines the best suited active sites for any given input set of dependent parameters. The equation can further be used to predict the product yield with the known values of active sites for a reaction. Among several Sn containing mixed oxides, Sn-Ni oxide (Sn-Ni-O) was found to be the better performing catalyst. The studies indicate that the formation of new defect sites when NiO and SnO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> are in the mixed state and possibly a solid solution enhances the catalytic efficiency. There are two main reasons for improved catalytic performance; one, mixing of SnO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> into NiO which reduces the number of holes (h<span style="font-size: 13.5px; line-height: 0; position: relative; top: -0.5em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">+<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">) localized on lattice oxygen (O<span style="font-size: 13.5px; line-height: 0; position: relative; top: -0.5em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2−<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">+ h<span style="font-size: 13.5px; line-height: 0; position: relative; top: -0.5em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">+<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">→ O<span style="font-size: 13.5px; line-height: 0; position: relative; top: -0.5em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">•−<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">) and two, smaller SnO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> particles are dispersed on the bigger particle NiO which alters the acidic and basic active sites in the catalyst. FT-IR adsorption study with amine and CO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> helped in deriving a plausible mechanism for this reaction. Under optimized reaction condition, Sn1.1-Ni-O-600 gave 77.3% of n-butylamine conversion and 75.7% of yield for 1,3-dibutylurea. The versatility of the catalyst was tested for carbonylation of different aliphatic and aromatic amines, diamine and hydroxy amine with CO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">.
Keywords: amines; CO2; Mixed oxide catalyst and bi-functional catalyst; Substituted urea

Green synthesis of xanthene and acridine-based heterocycles of pharmaceutical importance: a review - Burange, Anand S.; Gadam, Komal G.; Tugaonkar, Prajyot S.; Thakur, Seema D.; Soni, Ravish K.; Khan, Rubej R.; Tai, Mubashira S.; Gopinath, Chinnakonda S. (Environmental Chemistry Letters, 2021)
Xanthene and acridine-based heterocyclic compounds find applications in cancer chemotherapy, biological staining and laser dyes and are known for their antibacterial and anti-tumor properties. Here we review green catalytic routes for the synthesis of 1,8-dioxo-octahydroxanthenes, 1,8-dioxo-decahydroacridines and related heterocyclic molecules with catalysts such as metal oxides, mixed metal oxides, resins, supported organocatalysts, heteropolyacids, carbon-based materials, zeolites, sulfides and ionic liquids. We compare protocols for their catalytic activities, and proposed mechanisms are discussed.
Keywords: green chemistry; heterocycles; heterogeneous catalysis; Metal oxides; nanocatalysis